Avaliação da qualidade da água purificada em farmácias magistrais da região de São José do Rio Preto, SP - Moreno, A. H. [UNESP]; Tozo, G. C G [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (My University, 2011)
Water is the raw material used most in the production of diverse pharmaceutical forms and, being a constituent of the formulation itself, is subject to a number of physico-chemical and microbiological specifications. In addition, it is indispensable for laboratory tests and the cleaning of equipment and apparatus. The aim of this study was to ascertain the degree of physicochemical and microbiological contamination of purified water used in compounding pharmacies in the city of São José do Rio Preto, SP, Brazil. Samples were taken as recommended in the USP Pharmacopeia, with careful aseptic technique, and sent immediately the to quality control laboratory. Physicochemical properties were analyzed, including appearance, pH, conductivity, residue after evaporation, ammonia, calcium, chloride, heavy metals, sulfate and oxidizable substances, and microbiological tests were performed: total aerobic microbial count and detection of total and thermotolerant coliforms and Pseudomonas aeruginosa. Results showed that some parameters did not conform to the standards, especially pH, conductivity, inorganic impurities, oxidizable substances and microbiological test data, in 10%, 17%, 10%, 14% and 20% of the analyzed samples, respectively, This points to the need for greater care in the production and/or storage of purified water in these pharmaceutical establishments.

A água é a matéria-prima mais utilizada na produção de várias formas farmacêuticas, sendo um constituinte da própria formulação e exigindo para tal uma série de especificações físico-químicas e microbiológicas. Além disso, é um insumo de utilização imprescindível para testes laboratoriais e procedimentos de limpeza de equipamentos e utensílios. O presente trabalho teve como objetivo verificar o grau de contaminação química e microbiana em água purificada utilizada em farmácias magistrais da região de São José do Rio Preto, SP. As coletas foram realizadas segundo recomendações da USP Pharmacopeia, com os devidos cuidados de assepsia, e as amostras encaminhadas imediatamente ao laboratório de controle de qualidade. Foram analisados vários parâmetros físico-químicos, tais como aspecto, pH, condutividade, resíduo por evaporação, amônia, cálcio, cloreto, metais pesados, sulfato e substâncias oxidáveis, além de parâmetros microbiológicos, como contagem total de aeróbios e pesquisa de coliformes totais e termotolerantes e Pseudomonas aeruginosa. Os resultados indicaram alguns parâmetros de não conformidade: em 10% das amostras analisadas para o pH e pesquisa de impurezas inorgânicas, em 17% para condutividade, em 14% para substâncias oxidáveis e em 20% para análise microbiológica, ressaltando a necessidade de maior rigor na produção e qualidade da água purificada produzida e/ou armazenada nesses estabelecimentos farmacêuticos.
Quality assessment of purified water used in pharmacies in São José do Rio Preto, SP
Keywords: Impurity tests; Microbiological tests; Pharmacies; Purified water; Quality control; ammonia; calcium; chloride; heavy metal; sulfate; water; aerobic bacterium; Brazil; conductance; evaporation; laboratory; microbial contamination; microbiological examination; microorganism detection; nonhuman; pH; pharmacy; physicochemical model; Pseudomonas aeruginosa; quality control; water analysis